Seat of Empire : The Embattled Birth of Austin, Texas - Kerr, Jeffrey Stuart, 1957- (Book collections on Project MUSE., 2013)
This book recounts the history of the controversial founding of Austin as the capital of Texas. -- Provided by publisher.